Pola Komunikasi Customer Service Dengan Customer di Galeri PT. Indosat Ooredoo Supermall Karawaci Tangerang Dalam Meningkatkan Penjualan - Ghabrella Herdiani; Halomoan Harahap (Jurnal Ilmiah Wahana Pendidikan, 2023)
Face to face communication patterns and media communication patterns at Gallery of PTIndosat Ooredoo, Supermall Karawaci, Tangerang, can increase sales. Customers can better understand the aims and objectives from customer service by using face to face communication patterns and media in the context of marketing communication. This research method uses participant observation conducted by researchers and indepth interviews. This type of research uses Qualitative research methods. The result of the research that have been obtained are the implementation of the role of the customer service and customers at the Gallery of PT Indosat Ooredoo, Supermall Karawaci, Tangerang, for increasing sales.